Surprised by Sound : Rhyme's Inner Workings - Tartakovsky, Roi (Book collections on Project MUSE., 2021)
"Roi Tartakovsky's "Surprised by Sound" shows that the power of rhyme endures well into the twentieth and twenty-first centuries, even though its exemplary usages, such as in hip hop, may differ from traditional or expected forms. His work uncovers the mechanics of rhyme, revealing how and why it remains a vital part of poetry with connections to large questions about poetic freedom, cognitive mechanisms, and the accidental aspects of language. Surprised by Sound contributes to studies of sound in poetry by taking on two central questions. First, what is it about the structure of rhyme that makes it such a potent and ongoing source of poetic production and extra-poetic fascination? Second, how has rhyme changed and survived in the era of free verse, whose prototypical poetry is as hostile to meter and poetic diction as it is to the artificial-sounding thumping of rhyme at the end of every line? Tartakovsky approaches these key questions by theorizing and exemplifying a new category of rhyme that he terms "sporadic." As rhyme that is not systematized or expected, sporadic rhyme can be a single, strongly resounding rhyme that is used surprisingly in a contemporary free verse poem. It can also be an internal rhyme in a villanelle, or a few scattered rhymes unevenly distributed throughout a longer poem that nevertheless create a meaningful cluster of words. Tartakovsky locates sporadic rhyme in sources ranging from a sixteenth-century sonnet to a 2007 MoveOn.org ad in the New York Times. Gertrude Stein uses it in a nonsensical piece that would be nearly impossible to perform aloud, while hip-hop lyrics often deploy rhyming that is contingent precisely on the way words are pronounced and performed. Examining these usages across varied poetic traditions, Tartakovsky argues that rhyme's enduring value lies in its paradoxical and unstable nature. He approaches rhyme as a dynamic manifestation in language, exploring a series of four antithetical pairings-rigid/pleasurable, organizing/disruptive, accidental/motivated, regressive/progressive-which underscore its capacity for creating poetic, cognitive, and psychic effects. "Surprised by Sound: Rhyme's Inner Workings" demonstrates that attuning to a text's soundscape informs, and in some cases even produces, the very basis of a meaningful encounter with a poem"--